Vyacheslav Ivanov’s Concept of the “Zvukoobraz” - Konstantin Yu. Lappo-Danilevskii (Литературный факт)
The paper investigates the concept of the “zvukoobraz” (sound-image) in literary-philosophical articles and lectures on poetics by Vyacheslav Ivanov, specifically its origins, meaning, and context. This term is closely connected with the “Lautbild” of Wilhelm Wundt, translated in Russian as “zvukovoi obraz” by Tadeusz Zieliński in his widely known article about the German philosopher (1901). Viktor Shklovsky, one of the leading theorists of Russian Formalism, also wrote about “zvukovye obrazy” in his paper “About Poetry and Zaum Language” (1916). Vyacheslav Ivanov’s concept of “zvukoobraz” emerged as a result of his confrontation with the ideas of the Russian Formalists, which is reflected in his survey “On the Latest Theoretical Research in the Field of the Artistic Expression” (1920; printed 1922), in his course on poetics given at Baku university (1922; repeated in 1923–1924), in his paper “About the problem of the Sound Image in Pushkin’s Poetry” (1925; printed 1930). Andrei Bely’s observations on Pushkin’s “zvukoobrazy” made in his article “Aaron’s Rod (About the Word in Poetry)” (1917) were also important for Vyacheslav Ivanov. Aiming to oppose the arguments of the Formalists, Ivanov revived Potebnja’s psychological theory of language by introducing the concept of the “zvukoobraz” (sound-image), by which he meant fundamental sound combinations that were initially connected with particular images. According to him, the emergence of the “zvukoobraz” is the first and the most significant moment in creating the word and poetic works.